Enhancing functional rice crackers with Rhizophora mucronata leaves origin Sangihe Islands: A novel approach to boost nutritional and antioxidant properties - Tanod, Wendy Alexander; Cahyono, Eko; Rieuwpassa, Frets Jonas; Ansar, Novalina Maya Sari; Sambeka, Yana; Ijong, Frans Gruber; Mandeno, Jefri Anthonius; Palawe, Jaka Frianto Putra (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
This study aims to develop rice crackers into a functional food enriched with mangrove leaves (Rhizophora mucronata) from the Sangihe Islands, Indonesia, to improve their nutritional and antioxidant capacities. Mangrove leaves were extracted and analyzed using Gas Chromatography-Mass Spectrometry (GC-MS), revealing 10 fatty acid-derived compound profiles. Rice crackers were produced by adding R. mucronata leaf pulp and evaluated for proximate composition (moisture, ash, protein, fat, carbohydrate, and energy), sensory characteristics, and antioxidant capacity. Proximate analysis showed that the rice crackers contained 12.62% protein, 18.51% fat, and 59.75% carbohydrate and complied with the Indonesian National Standard (SNI) for rice crackers regarding moisture content (5.71%). Sensory evaluation showed that rice crackers with added mangrove leaves were well accepted by panelists, with “like” to “very like” ratings for appearance, aroma, taste, and texture. The antioxidant capacity of rice crackers with the addition of mangrove leaves showed moderate activity (IC50 = 123.38 µg/mL) despite a decrease due to the frying process. This study concluded that R. mucronata leaves can be a potential functional ingredient, providing nutritional benefits and antioxidant properties in rice crackers.